Chinese Stock Market Response To COVID-19: An Example of An Event Study Method - Wang, Zeying (2022)
This thesis analyses the response of the Chinese stock market and eight sector-specific indices to the coronavirus disease 2019 in China. This research adopts an event study method, using the day of the Wuhan lockdown as the event date, (-130, -10) as the estimated window period and (0, 47) as the event window. The Shanghai Stock Exchange Composite Index, Consumer Staples, Emerging Industries, Energy, Environmental Protection, Healthcare, Financials, Telecommunications, and Transportation Services sector indices' abnormal returns and cumulative abnormal returns are calculated during the event window, and their statistical significance is determined based on t-values.